No effect of resveratrol supplementation after 6 months on insulin sensitivity in overweight adults: a randomized trial. Issue 4 (3rd June 2020) - de Ligt, Marlies; Bergman, Maaike; Fuentes, Rodrigo Mancilla; Essers, Hans; Moonen-Kornips, Esther; Havekes, Bas; Schrauwen-Hinderling, Vera B; Schrauwen, Patrick
ABSTRACT: Background: Effects of resveratrol on metabolic health have been studied in several short-term human clinical trials, with conflicting results. Next to dose, the duration of the clinical trials may explain the lack of effect in some studies, but long-term studies are still limited. Objectives: The objective of this study was to investigate the effects of 6-mo resveratrol supplementation on metabolic health outcome parameters. Methods: Forty-one overweight men and women (BMI: 27–35 kg/m 2 ; aged 40–70 y) completed the study. In this parallel-group, double-blind clinical trial, participants were randomized to receive either 150 mg/d of resveratrol ( n = 20) or placebo ( n = 21) for 6 mo. The primary outcome of the study was insulin sensitivity, using the Matsuda index. Secondary outcome measures were intrahepatic lipid (IHL) content, body composition, resting energy metabolism, blood pressure, plasma markers, physical performance, quality of life, and quality of sleep. Postintervention differences between the resveratrol and placebo arms were evaluated by ANCOVA adjusting for corresponding preintervention variables. Results: Preintervention, no differences were observed between the 2 treatment arms. Insulin sensitivity was not affected after 6 mo of resveratrol treatment (adjusted mean Matsuda index: 5.18 ± 0.35 in the resveratrol arm compared with 5.50 ± 0.34 in the placebo arm), although there was a significant difference in postintervention glycated hemoglobin (HbA1c) between the arms ( P = 0.007). The adjusted means showed that postintervention HbA1c was lower on resveratrol (35.8 ± 0.43 mmol/mol) compared with placebo (37.6 ± 0.44 mmol/mol). No postintervention differences were found in IHL, body composition, blood pressure, energy metabolism, physical performance, or quality of life and sleep between treatment arms. Conclusions: After 6 mo of resveratrol supplementation, insulin sensitivity was unaffected in the resveratrol arm compared with the placebo arm. Nonetheless, HbA1c was lower in overweight men and women in the resveratrol arm. This trial was registered at Clinicaltrials.gov as NCT02565979.